2020
DOI: 10.3390/nu12030618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Combination of Water-Soluble Coenzyme Q10 and Collagen on Skin Parameters and Condition: Results of a Randomised, Placebo-Controlled, Double-Blind Study

Abstract: Skin is a complex and dynamic organ that provides a protective interface between the external environment and the body; changes in skin appearance are often the first visible signs of aging. It is well established that nutrients and other bioactive substances have important roles in the structure and functions of human skin; however, the effects of dietary supplementation of such bioactives are much less investigated. The objective of this randomised, double-blind placebo-controlled study was to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 48 publications
2
28
0
5
Order By: Relevance
“…These results appear to reinforce the role that CoQ has in minimizing skin aging and are in line with the work from Zmitek et al conducted on human volunteers to demonstrate the important role that dietary intake of CoQ has on improving skin structural features associated with skin aging (mimic wrinkles/poor skin tone/visual dryness). On a cohort of 34 healthy female volunteers aged between 45–65 years, those receiving an investigational product for 12 weeks, based on a liquid food supplement, characterized by a combination of water-soluble CoQ (Q10Vital ® , 50 mg) and fish collagen (4.0 g), reported better skin parameters compared to placebo controls [ 150 ]. However, no significant effects of the supplementation on skin hydration, dermis thickness, transepidermal water loss (TEWL) and viscoelasticity were observed.…”
Section: Emerging Applications Of Coenzyme Q 10mentioning
confidence: 99%
“…These results appear to reinforce the role that CoQ has in minimizing skin aging and are in line with the work from Zmitek et al conducted on human volunteers to demonstrate the important role that dietary intake of CoQ has on improving skin structural features associated with skin aging (mimic wrinkles/poor skin tone/visual dryness). On a cohort of 34 healthy female volunteers aged between 45–65 years, those receiving an investigational product for 12 weeks, based on a liquid food supplement, characterized by a combination of water-soluble CoQ (Q10Vital ® , 50 mg) and fish collagen (4.0 g), reported better skin parameters compared to placebo controls [ 150 ]. However, no significant effects of the supplementation on skin hydration, dermis thickness, transepidermal water loss (TEWL) and viscoelasticity were observed.…”
Section: Emerging Applications Of Coenzyme Q 10mentioning
confidence: 99%
“…In a review study, Vollmer et al, (2018) [ 13 ] reported that oral administration of collagen peptides generally improves the characteristics of aged skin. In addition, Schwartz and Park (2012) [ 23 ], Genovese et al, (2017) [ 11 ], and Zmitek et al, (2020) [ 6 ] reported an improvement in the skin parameters related to skin microrelief and reduced facial aging signs associated with an increase in skin hydration after oral supplementation with hydrolyzed collagen.…”
Section: Discussionmentioning
confidence: 99%
“…This result revealed an increase in dermis density, greater formation of collagen fibrils, and repair of current damage, helping to reduce the chronological aging and photoaging process and improving the skin density [ 8 , 27 ]. An increase in dermis thickness was also observed and was correlated with hydration of deeper skin layers and with the maintenance of skin homeostasis, thus helping to reduce the damage caused by chronological aging and other factors [ 6 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations